Enfrentando a violência de gênero em Santarém: a perspectiva de agentes da DEAM sobre as etapas da Lei nº 11.340 - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2018)
The creation of Special Police in Assistance to Women can be perceived as a victory for increasingly aware society that can challenge and tackle domestic and family violence, however, the fear and ignorance of the procedures are very present in collective thinking. Through this research, I sought to present and expand on the steps that are followed within the DEAMs, guided by the law 11.340 / 2006 - Maria da Penha Law - to provide shelter and support women who seek this space to report violence to them was affected . For the research, supported me in articles and studies on the subject to guide the design of open questions to be presented to agents of the police station of women in the municipality of Santarém, the statements were analyzed and presented in the course of the discussion. The result of this monograph was the description of the steps followed, within the scope of the DEAM, by women seeking to secure their rights.
Keywords: DEAM; Enfrentamento; Etapas; Mulher; CNPQ:: CIÊNCIAS HUMANAS